Autism spectrum disorder: Presentation and prevalence in a nationally representative Australian sample. (March 2016) - Randall, Melinda; Sciberras, Emma; Brignell, Amanda; Ihsen, Elfriede; Efron, Daryl; Dissanayake, Cheryl; Williams, Katrina
Objective: The aim of this study was to identify the prevalence of parent-reported autism spectrum disorder diagnosis in Australia, and examine the developmental profile of children with autism spectrum disorder compared to their peers. Design/Setting: Secondary analyses were undertaken on data from the Longitudinal Study of Australian Children. Participants: Children were recruited at kindergarten (K cohort) and birth (B cohort), and subsequently completed two-yearly 'waves' of assessments. Main Outcomes: Autism spectrum disorder diagnostic status was ascertained at Wave 4 along with age of diagnosis by parent report. Standardised tools were used to assess children's quality of life, behaviour, receptive vocabulary and non-verbal intelligence. Results: Prevalence of autism spectrum disorder was 2.5% (95% confidence interval = [2.0, 3.0]) in the B cohort compared to 1.5% (95% confidence interval = [1.2, 2.0]) in the K cohort. In both cohorts, children with autism spectrum disorder had poorer mean quality of life, emotional-behavioural functioning and receptive vocabulary compared with non-autism spectrum disorder peers, and a higher proportion of children with autism spectrum disorder had problems in these areas. However, between 6% and 9% of children with moderate to severe autism spectrum disorder and 12–20% with mild autism spectrum disorder were not reported to have problems with social interaction. Conclusion: The prevalence of a parent-reported diagnosis of autism spectrum disorder before age 7 in Australia was higher in the B cohort. Data from future Longitudinal Study of Australian Children waves will clarify whether autism spectrum disorder has been diagnosed earlier in the B cohort or if there is a continued increase in prevalence. Future waves will also provide crucial information about the types and severity of problems experienced during the primary and secondary school years which will assist service planning.